2018
DOI: 10.1007/s00384-018-3155-y
|View full text |Cite|
|
Sign up to set email alerts
|

Mucosal advancement flap for recurrent complex anal fistula: a repeatable procedure

Abstract: MAF is effective for treatment of complex recurrent AF. A pre-existing MAF procedure does not worsen the healing rate of the second flap. The rate of surgical complications is similar with those reported in the literature for MAFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…This is a comparative study on this subject. In the past, most studies dealt with either only CD patients or only cryptoglandular stulas 7,24,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a comparative study on this subject. In the past, most studies dealt with either only CD patients or only cryptoglandular stulas 7,24,27 .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of treatment options exist, including stulotomy for super cial stula course or seton drainage 4,5 . Fistula closure can also be performed by surgical reconstructive and sphincter preserving methods like mucosal or submucosal rectal advancement ap or LIFT (ligation of intersphinteric stula tract) procedure [6][7][8][9] . The results after LIFT or advanced ap were examined separately in a large review for cryptoglandular and CD stulas with a comparable result 9 .…”
mentioning
confidence: 99%
“…Recurrence of the disease in both seton placement and rectal advancement flap methods can be due to the surgeon's inadequate experience and failure to diagnose internal fistula hole, horseshoe fistula, nicotine use by the patient, and a history of chronic constipation. [1415] Moreover, among the reasons for the increased recurrence of anal fistula in the seton placement were the type of seton material, lack of sufficient drainage from the internal fistula hole, and the discharge from the external fistula hole. [15] In contrast to the observed results, in the study of Ege et al (2014), the rate of recurrence of anal fistula disease in seton placement technique was lower than that of rectal advancement flap, which could be due to the difference in the type of seton material.…”
Section: Discussionmentioning
confidence: 99%
“…[1415] Moreover, among the reasons for the increased recurrence of anal fistula in the seton placement were the type of seton material, lack of sufficient drainage from the internal fistula hole, and the discharge from the external fistula hole. [15] In contrast to the observed results, in the study of Ege et al (2014), the rate of recurrence of anal fistula disease in seton placement technique was lower than that of rectal advancement flap, which could be due to the difference in the type of seton material. [16] In addition, in contrast to the results of the present study, van der Hagen et al (2011) reported that the rate of anal fistula recurrence in rectal advancement flap method was higher than the seton placement technique.…”
Section: Discussionmentioning
confidence: 99%
“…Podetta 18 en 2018, describe el uso colgajo de avance de mucosa posterior a recidiva en pacientes que ya fueron sometidos colgajo previamente. El éxito al primer intento fue un 66,1%, en el grupo con segundo intento 78,1%.…”
Section: Colgajo Endorrectal De Avance (Cera)unclassified